Non‐severe COVID‐19 is associated with endothelial damage and hypercoagulability despite pharmacological thromboprophylaxis. (13th February 2022) - Kelliher, Sarah; Weiss, Luisa; Cullivan, Sarah; O'Rourke, Ellen; Murphy, Claire A.; Toolan, Shane; Lennon, Áine; Szklanna, Paulina B.; Comer, Shane P.; Macleod, Hayley; Le Chevillier, Ana; Gaine, Sean; et al.
Abstract: Background: Hypercoagulability and endothelial dysfunction are hallmarks of coronavirus disease 2019 (COVID‐19) and appear to predict disease severity. A high incidence of thrombosis despite thromboprophylaxis is reported in patients with moderate to severe COVID‐19. Recent randomized clinical trials suggest that therapeutic‐intensity heparin confers a survival benefit in moderate‐severity COVID‐19 compared to standard‐intensity heparin, potentially by harnessing heparin‐mediated endothelial‐stabilizing and anti‐inflammatory effects. Objective: We hypothesized that patients with moderate‐severity COVID‐19 exhibit enhanced hypercoagulability despite standard‐intensity thromboprophylaxis with low molecular weight heparin (LMWH) compared to non‐COVID‐19 hospitalized patients. Methods: Patients with moderate COVID‐19 and a control group (severe acute respiratory syndrome coronavirus 2 [SARS‐CoV‐2]–negative hospitalized patients) receiving LMWH thromboprophylaxis were recruited. Markers of endothelial damage and plasma thrombin generation parameters were assessed. Results: Tissue plasminogen activator levels were significantly increased in the COVID‐19 group (8.3 ± 4.4 vs. 4.9 ± 2.4 ng/ml; P = .02) compared to non‐COVID‐19–hospitalized patients. Despite thromboprophylaxis, mean endogenous thrombin potential was significantly increased among COVID‐19 patients (1929 ± 448 vs. 1528 ± 460.8 nM*min; P = .04) but lag time to thrombin generation was significantly prolonged (8.1 ± 1.8 vs. 6.2 ± 1.8 mins; P = .02). While tissue factor pathway inhibitor (TFPI) levels were similar in both groups, in the presence of an inhibitory anti‐TFPI antibody, the difference in lag time between the groups was abrogated. Conclusions: Collectively, these data demonstrate that COVID‐19 of moderate severity is associated with increased plasma thrombin generation and endothelial damage, and that hypercoagulability persists despite standard LMWH thromboprophylaxis. These findings may be of clinical interest given recent clinical trial data which suggest escalated heparin dosing in non‐severe COVID‐19 may be associated with improved clinical outcomes.